Improving child health service interventions through a Theory of Change: A scoping review - Jones, Benjamin; Paterson, Amy; English, Mike; Nagraj, Shobhana (Frontiers in Pediatrics, 2023)
Background: The objective of this scoping review was to map how child health service interventions develop, utilise, and refine theories of change. A theory of change (ToC) is a tool for designing, implementing, and evaluating interventions that is being increasingly used by child health practitioners who are aiming to enact change in health services. Methods: A published protocol guided this scoping review. Relevant publications were identified through selected electronic databases and grey literature via a search strategy. The main inclusion criteria were any child health service intervention globally that described their ToC or ToC development process. These were applied by two independent reviewers. Data relevant to the research sub-questions were extracted, charted and discussed. Findings: 38 studies were included in the analysis. This scoping review highlights the disparate and inconsistent use, and reporting of ToCs in the child health service intervention literature. Conclusion: A ToC may be a helpful tool to enact change in a child health service but careful consideration must be undertaken by the child health service regarding how to maximise the benefits of doing a ToC, and how to accurately report it.